2009
DOI: 10.26719/2009.15.4.827
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypertension among the adult Moroccan population

Abstract: This study used data from the Moroccan national survey in 2000 to identify the principle risk factors for hypertension in a representative sample of the population age 20+ years. The risk of hypertension increased steadily with age and was higher among rural residents (OR = 1.42) and those with diabetes (OR = 1.72). The risk increased with increased body mass index, waist size and hypercholesterolaemia. The risk of hypertension decreased by 36% and 46% respectively for those who walked 30-60 min and > 60 min d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Our results confirms that hypertension prevalence was high among individuals from rural area compared to urban area, based on data collected by the ministry of health in 2000 (32). A recent meta-analysis study showed that prevalence estimates of hypertension were higher in urban communities, compared to participants in rural settings in Latin America, Asia and Sub-Saharan Africa (33).…”
Section: Discussionsupporting
confidence: 88%
“…Our results confirms that hypertension prevalence was high among individuals from rural area compared to urban area, based on data collected by the ministry of health in 2000 (32). A recent meta-analysis study showed that prevalence estimates of hypertension were higher in urban communities, compared to participants in rural settings in Latin America, Asia and Sub-Saharan Africa (33).…”
Section: Discussionsupporting
confidence: 88%
“…Similar observations were also reported in studies conducted. 1,9 In present study 76.7% of study population reported burden of medication therapy as a reason like the study conducted. 10 As Medicines are available in different dosage form they can also influences medication adherence behavior of the patients.…”
Section: Figure 2bmentioning
confidence: 48%
“…A total of 25 studies from 23 available articles with 334,468 patients (41,713 cases) were included in the present meta‐analysis, because two articles included two studies independently . Among these studies, two studies were carried out in the United States, 13 in Asia, five in Europe, and five in Africa . As for study design, there were three cohort studies, two case‐control studies, and 20 cross‐sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, two studies were carried out in the United States, 13 in Asia, five in Europe, and five in Africa . As for study design, there were three cohort studies, two case‐control studies, and 20 cross‐sectional studies. The baseline characteristics of the studies are shown in the Table.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation